2022
DOI: 10.1101/2022.02.13.480270
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The V-type H+-ATPase is targeted in anti-diuretic hormone control of the Malpighian ‘renal’ tubules

Abstract: Like other insects, secretion by mosquito MTs is driven by the V-type H+-ATPase (VA), which is densely packed in the apical membrane of principal cells. The anti-diuretic neurohormone CAPA inhibits tubule secretion stimulated by select diuretic hormones; however, the cellular effectors of this inhibitory signaling cascade remain unclear. Herein, we show that the VA inhibitor bafilomycin selectively inhibits serotonin (5HT)- and calcitonin-related diuretic hormone (DH31)-stimulated secretion. VA activity increa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 108 publications
(313 reference statements)
0
3
0
Order By: Relevance
“…For instance, in the locust Schistocerca gregaria , ITPa but not ITPL promotes ion and water reabsorption across the hindgut (Audsley et al ., 1992a, Audsley et al ., 1992b, King et al ., 1999, Wang et al ., 2000), thereby promoting anti-diuresis. Previous experiments have shown that the MTs are also targeted by anti-diuretic hormones: CAPA neuropeptides inhibit diuresis in some insects including Drosophila via direct hormonal actions on the renal tubules (Paluzzi et al ., 2008, MacMillan et al ., 2018, Sajadi et al ., 2020, Sajadi et al ., 2023). Given the expression of Gyc76C, a putative ITP receptor, in both the hindgut and renal tubules, ITP could modulate osmotic and/or ionic homeostasis by targeting these two excretory organs.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, in the locust Schistocerca gregaria , ITPa but not ITPL promotes ion and water reabsorption across the hindgut (Audsley et al ., 1992a, Audsley et al ., 1992b, King et al ., 1999, Wang et al ., 2000), thereby promoting anti-diuresis. Previous experiments have shown that the MTs are also targeted by anti-diuretic hormones: CAPA neuropeptides inhibit diuresis in some insects including Drosophila via direct hormonal actions on the renal tubules (Paluzzi et al ., 2008, MacMillan et al ., 2018, Sajadi et al ., 2020, Sajadi et al ., 2023). Given the expression of Gyc76C, a putative ITP receptor, in both the hindgut and renal tubules, ITP could modulate osmotic and/or ionic homeostasis by targeting these two excretory organs.…”
Section: Resultsmentioning
confidence: 99%
“…The MTs, which are functional analogs of vertebrate kidneys, are responsible for the formation of primary urine (Coast, 2007), driven by the V-type H + -ATPase (Wieczorek, 1992) that permits transport of Na + and K + cations across the membrane (Beyenbach, 2003) via a putative H + /cation exchanger (Wieczorek et al, 2009). The MTs are regulated by various diuretic and anti-diuretic hormones, which in A. aegypti includes the biogenic amine 5-hydroxytryptamine (5HT) (Clark and Bradley, 1998; Veenstra, 1988), DH 31 (Coast et al, 2005), DH 44 (Clark et al, 1998; Clark et al, 1998), kinin-like peptides (Lu et al, 2011; Pietrantonio et al, 2005) and CAPA that inhibits the activity of select diuretic hormones (Sajadi et al, 2018; Sajadi et al, 2020; Sajadi et al, 2023). The primary urine then enters the hindgut, where it is further modified through secretory and reabsorptive processes.…”
Section: Discussionmentioning
confidence: 99%
“…All study data are openly available at https://doi.org/10.5683/SP3/PADHU5 ( 83 ). All other data is included in the article and/or SI Appendix .…”
Section: Data Materials and Software Availabilitymentioning
confidence: 99%